Pengaruh Kegiatan Montase Terhadap Kemampuan Motorik Halus Anak - Haerul Annuar; Besse Nirmala; Nurhukma Samarto (Jurnal Kreatif Online, 2021)
The montage activity is a work of art produced by children by cutting from several sources and then pasting them into new images with certain themes. The purpose of this study was to determine the effect of montage activities on children's fine motor skills. This research is an experimental research. The experimental method is a method that provides and uses a phenomenon called an exercise or experiment, and is the most appropriate method for investigating causal relationships. Data collection techniques are carried out through observation, interviews, and documentation. Furthermore, data processing was carried out by using the percentage technique and the t test, the t value ≥ t table (12,291 ≥ 1,724) was obtained. So it can be concluded that H is rejected and H1 is accepted, which means that there is an effect of montage activities on the fine motor skills of children in Group B TK Widyatama Tadulako, Mantikulore District. Based on the research results, it is expected that teachers can stimulate children's fine motor skills through montage activities.